Paracetamol: Therapeutic Use and the Problem of Acute Intoxications - Ye. M. Shifman; A. L. Yershov (Общая реаниматология)
As a review of literature, the authors discuss the mechanisms of action and the therapeutic use of paracetamol, one of the most known and widely used drugs. In 1995, the WHO experts comparatively evaluated drugs from different groups, which have a combined analgesic and antipyretic activity. Paracetamol holds the lead in its efficacy/safety. An interest in the mechanism of action of the drug, as well as discussion of its safe use have again quickened due to the given ability to administer intravenous paracetamol for postoperative analgesia. Based on the review of literature, the authors draw a conclusion that paracetamol may be successfully used in practice of an intensive care unit. This drug has rather marked intrinsic analgesic and antipyretic effects and its coadministration with narcotic analgesics leads to synergism and reduces needs for opioids. When used in therapeutic doses, paracetamol is practically safe, but requires that a weighed approach be applied to its use in risk-group patients.